Utilization of Remote Sensing and Geographic Information System to Identify Buffer Zones Area at Plumpang Fuel Depot - Setiawan, Cahyadi; Hardi, Ode Sofyan; A'Rachman, Fauzi Ramadhoan; Nabilla, Lyzia; Wiranata, Andi; Furqon, Zidan; Salsabillah, Fadia; Maulana, Ibnu Adam; Wardana, Muhammad Wahyu; Deffry, Muhammad (Indonesian Journal of Geography, 2024)
Plumpang is a national vital object surrounded by residential areas in its vicinity. This study aims to identify buffer zones at the Pertamina Plumpang BBM Depot. The method used in this research is Spatio Temporal Analysis with secondary data from the land-use map of Jakarta, Google Earth imagery from 2002 to 2022, and Landsat 4 imagery from 1990. The results show that at distances of 50 meters, 50-100 meters, and 100-250 meters, there are 503, 870, and 2554 buildings, respectively. Furthermore, these buildings are predominantly very dense residential areas. Due to the highly concentrated population and the proximity to the depot, the area faces a high risk of fire disasters given the flammable nature of the fuel. The proximity of the settlement to the fuel depot has a direct correlation with the heightened risk of a fire disaster. The buffer zone distance used in the range of 50 - 100 meters to ensure the safety of the population from potential fire disasters. The designated buffer zone can be effectively transformed into a hydrological flow or water channel serving as a separator and barrier between the fuel depot and residential areas.